Desempenho de métodos na estimativa de evapotranspiração de referência para o estado da paraíba, brasil - De Figueredo Dantas, Geffson [UNESP]; De Oliveira, Vinicius Mendes Rodrigues; Dalri, Alexandre Barcellos [UNESP]; Palaretti, Luiz Fabiano [UNESP]; Dos Santos, Miqueias Gomes [UNESP]; De Faria, Rogério Texeira [UNESP] (My University, 2016)
The standard method for estimating reference evapotranspiration (ET0), FAO Penman-Monteith (PM) employs meteorological variables which are not always available to most farmers. Thus, this study aimed to evaluate and benchmark their performance if necessary, to the conditions of Paraíba, different methods for daily ET0 were estimated by comparing them with the standard FAO Penman-Monteith method. We used a time period of 17 years of weather data INMET in four cities in the state of Paraíba. The methods evaluated were the Hargreaves-Samani (HS), Blaney-Criddle (BC), Camargo (C) and Jensen-Haise (JH). For comparative analysis between the PM method and other methods, correlation analysis and linear regression to determine the coefficients of the equation (Y = a + bx) and the coefficient of determination (R²) was performed. For accuracy of empirical methods, the analysis was performed to determine the level of agreement (d) and performance index (c). The estimation of reference evapotranspiration, obtained by four empirical for meso-Paraíba PB methods, achieved satisfactory performance, the HS method for the rough mesoregion needed no adjustments since the JH, C and HS methods for meso coast, borborema and hinterland need adjustment for better accuracy compared to the standard method.
Performance of methods for estimating ET0 in paraÍba state, Brazil
Keywords: Calibration; Evapotranspiration; Irrigation